2007
DOI: 10.4049/jimmunol.179.8.5407
|View full text |Cite
|
Sign up to set email alerts
|

Gr-1high Polymorphonuclear Leukocytes and NK Cells Act via IL-15 to Clear Intracellular Haemophilus influenzae in Experimental Murine Peritonitis and Pneumonia

Abstract: Polymorphonuclear leukocytes (PMNs) can be divided into Gr-1high and Gr-1low subpopulations, but the differences in the functions of these cells in the host are unknown. This study investigated the roles of these two cell populations in the clearance of an intracellular pathogen (Haemophilus influenzae) causing murine peritonitis and pneumonia. Microarray analysis and quantitative real-time PCR analysis of proteose peptone-elicited peritoneal murine PMNs showed that IL-15 mRNA levels were significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 48 publications
2
20
1
Order By: Relevance
“…5). This is consistent with the finding that neutrophils are involved in the activation and maintenance of NK cells during influenza virus infection (62) and with neutrophil cytokines such as IL-15 promoting survival and trafficking to sites of infection (63)(64)(65). Moreover, activated NK cells express high concentrations of IFN-␥ after interaction with NKp46 and sugar residues expressed on the surface of the HA protein (66).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…5). This is consistent with the finding that neutrophils are involved in the activation and maintenance of NK cells during influenza virus infection (62) and with neutrophil cytokines such as IL-15 promoting survival and trafficking to sites of infection (63)(64)(65). Moreover, activated NK cells express high concentrations of IFN-␥ after interaction with NKp46 and sugar residues expressed on the surface of the HA protein (66).…”
Section: Resultssupporting
confidence: 78%
“…Neutrophil-depleted mice have impaired NK cell maturation exhibiting hyperproliferation and weak survival (80). Neutrophils also express high levels of IL-15, which promotes NK cell activation (63)(64)(65). Early recruitment of neutrophils by PA likely mediates the activation and maintenance of NK cells observed at 4 days p.i.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that bacterial counts were higher in blood, liver, and peritoneum after NK cell depletion at 4 h after CLP, but that bacterial numbers were not different between control and NK cell-deficient mice at 18 h, the time point used in our studies. Other reports have shown that NK cells contribute to bacterial clearance in experimental models of E. coli, H. influenza, and L. monocytogenes infection, among others (31)(32). Therefore, NK cells appear to be an important component of the host response to infection in many circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…We employed four-color FACS to distinguish different immunocyte populations: CD45 as a marker for nucleated hematopoietic cells (31), CD11b as a marker for macrophage/microglia (32), F4/80 as a mature macrophage marker (33), and GR1 as a neutrophil marker in peripheral organs (34). The splenocytes isolated from control animals contained 11.05 Ϯ 1.96% CD45 ϩ CD11b high macrophages/granulocytes of all CD45 ϩ lymphocytes (Fig.…”
Section: Sox2mentioning
confidence: 99%